(untitled) (City Dental College Journal, 2012)
A quasi-experimental study was carried out to assess the knowledge on HIV/ AIDS among women in Boro Chondrail & Barigaon village of Savar district from 19th April to 25th April 2009. A total of 77 women were selected purposively. Baseline data were collected through pretested structured questionnaires by face to face interview. Educational intervention was given and data were collected again using the same questionnaires. Only 49.35% heard the name of HIV /AIDS before the program. Among the respondents 18.42% heard the name of AIDS from television, 5.26% were from radio, 2.64% were from newspaper, 5.26% were from sign board and 68.42% were health workers. About the mode of transmission 29.87% said that HIV transmits by sharing syringe & needle, 31.17% answered unsafe physical relation, 16.88% said by blood of infected person, 5.19% knew about vertical transmission and 5.19% said by breast milk before intervention. After intervention 100% said that HIV transmits by sharing syringe & needle, 100% answered unsafe physical relation, 100% told by blood of infected person, 77.92% reported vertically transmission and 88.31% said through breast milk. Majority (70.13%) didnt know about the symptoms of AIDS before intervention. Only 11.69% identified weight loss as symptom of AIDS, 7.79% answered fever & cough, 28.69% told weakness, 1.30% mentioned diarrhoea. After intervention which were improved to 35.06%, 32.46%, 32.46%, 35.06%, 19.48%, 19.48% respectively. Before intervention 23.38% believed living in same house with an AIDS patient could infect others, 31.17% believed use same drinking glass and 14.29% believed eating together could infect others. After intervention no one found who believed in myth about AIDS. Among the respondents only 46.75% knew the role of condom in prevention of AIDS before intervention and it became 100% after the intervention. Only 12.58% knew intravenous drug users are the risk group with increased to 93.5% after the intervention. It may be concluded that the knowledge of rural women on HIV/AIDS were not good which raised significantly after the educational intervention. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11830 City Dental College Journal Vol.9(1) 2012 7-11